Rice residue management in wheat under different tillage practices and nitrogen doses - Kumar, Arvind; Jat, M.L.; Kumar, Ashok; Tomar, Jaibir; Kumar, Sudhir; Kushwaha, S.R. (Annals of Agricultural Research, 2016)
A field experiment on sandy loam was conducted during rabi 2005-06 and 2006-07 at the researchfarm of the Janta Vedic (P.G.) College, Baraut, district-Baghpat (U.P.) to study the growth, yield andeconomics of wheat (Triticum aestivum L.) under different rice residue and zero and conventionaltillage practices in main plots and four nitrogen levels (0, 50 kg, 100 kg and 150 kg N/ha) in subplots replicated crops. Residue retained with zero tillage recorded significantly higher yield attributesas well as grain and straw yield over other residue and tillage management. The increasing rate ofnitrogen at higher dose (150 kg N/ha and 100 kg N/ha) produced significantly higher grain weight/spike as compared to 50 kg N/ha application. The higher rates of nitrogen application showedsignificantly better grain and straw yield as compared to lower levels of nitrogen application. Netreturn (Rs. 31,865 and 30,126 Rs /ha) and B:C ratio (1.94 and 1.75) were also recorded maximumunder residue retained with zero tillage during 2005-06 and 2006-07, respectively. The higher rateof nitrogen (150 kg N/ha) gave higher net profit (35,272 and 33,604 Rs/ha), highest B:C ratio (1.86and 1.69) during respective years.